(3GdUhGYb GdeMQbI dENhGf GdVdGd hGdEHJOGY hGdRfObIs - (3CMeO Hf eMeO Hf Ydj Hf nMnLQ GdngrjnJej GdSYOj GdCfUGQj, TgGH GdOjf TjN GdESdGe, CHh GdYHGS,J (B974 (3g` s
(3ChdgG (B:s
(3CeG HYO aEfj bO oSFdJ bOjekG aj JCdja cJGH jHjf MbjbI NdGaI GdUOjb hEeGQI GHf GdNWGH aCLHJ Edi Pdc s
(3BNQgG (B:s
(3hBNQ OYhGge Cf GdMeO ddg QH GdYGdejf SHMGf QHc QH GdYRI YeG jUahf hSdGe Ydi GdeQSdjf Je GdcJGH GdeSei HGdUhGYb s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B234 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B152s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1083s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3GdMOjK h GdeUWdMs